KAJIAN ROMANTISME PADA NOVEL GARIS LUKA KARYA KHAIRANI HASAN - Noviani, Dela; Effendy, Chairil; Wartiningsih, Agus (Universitas Tanjungpura, 2025)
This study aims to describe the results of the analysis of the six characteristics of romanticism in the novel Garis luka by Khairani Hasan. The research method used in this study is a descriptive method with a qualitative research form. The approach used in this research is an objective approach. Sources of data in this study, namely in the form of documents in the form of a novel. The technique used in this research is a documentary study technique. The tools used in this study were writing instruments and laptops. The results of this study indicate that romanticism includes a return to nature, moodiness or melancholy, primitivism, sentimentalism individualism, and exoticism. This research is related to the independent curriculum for the subject of Indonesian Language and Literature at the SMA level, class XII, odd semester. The results of this study are expected to be used by teachers as teaching materials in schools related to literature.